2017
DOI: 10.1016/j.jamcollsurg.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Did Pre-Affordable Care Act Medicaid Expansion Increase Access to Surgical Cancer Care?

Abstract: BACKGROUND Although the Affordable Care Act (ACA) expanded Medicaid access, it is unknown whether this has led to greater access to complex surgical care. Evidence on the effect of Medicaid expansion on access to surgical cancer care, a proxy for complex care, is sparse. Using New York’s 2001 statewide Medicaid expansion as a natural experiment, we investigated how expansion affected use of surgical cancer care among beneficiaries overall and among racial minorities. STUDY DESIGN From the New York State Inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 16 publications
(18 reference statements)
1
27
0
Order By: Relevance
“…Additionally, the percentage of uninsured patients dropped by 21.3% immediately after the expansion ( P <.01). 13 Furthermore, Loehrer et al evaluated Massachusetts 2006 insurance expansion and found that patients with government-subsidized or self-pay had a 44% increased rate of resection (IRR 1.44; 95% CI, 1.23–1.68, P <.001), a 6.21 percentage point decreased probability of emergent admission (95% CI, 211.88–20.54, P .032), and an 8.13 percentage point increased probability of an elective admission (95% CI, 1.34–14.91, P =.019) compared with the control states. 7 Similarly, we found that Medicaid expansion increased surgical access to cancer patients for surgeries such as lung (IRR 1.30; P <.01), breast (IRR 1.25; P <.02), and colorectal resection (IRR 1.25; P <.001).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the percentage of uninsured patients dropped by 21.3% immediately after the expansion ( P <.01). 13 Furthermore, Loehrer et al evaluated Massachusetts 2006 insurance expansion and found that patients with government-subsidized or self-pay had a 44% increased rate of resection (IRR 1.44; 95% CI, 1.23–1.68, P <.001), a 6.21 percentage point decreased probability of emergent admission (95% CI, 211.88–20.54, P .032), and an 8.13 percentage point increased probability of an elective admission (95% CI, 1.34–14.91, P =.019) compared with the control states. 7 Similarly, we found that Medicaid expansion increased surgical access to cancer patients for surgeries such as lung (IRR 1.30; P <.01), breast (IRR 1.25; P <.02), and colorectal resection (IRR 1.25; P <.001).…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, they found that the Medicaid expansion versus nonexpanded states did not have any significant difference in access to care. 34 Multiple other studies 2,21,26 have looked at access to care for orthopaedics among other subspecialties. A previous study 35 showed that Medicaid patients with operative ankle fractures had similar difficulty scheduling an appointment.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple other studies 2 , 21 , 26 have looked at access to care for orthopaedics among other subspecialties. A previous study 35 showed that Medicaid patients with operative ankle fractures had similar difficulty scheduling an appointment.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the effect of the 2005 Medicaid disenrollment in Tennessee, which resulted in the later stage of disease at diagnosis of breast cancer and decreased delays to treatment 12 . As studies continue to evaluate the complex interactions between healthcare reform and cancer care, 13 we have attempted to understand other factors related to treatment delays.…”
Section: Discussionmentioning
confidence: 99%